Islamic Religious Education Teacher Mindset Towards Golden Indonesia 2045 And Demographic Dividinet 2050 - Anwar, Ade Chairil (Fahmina: Jurnal Pendidikan Islam, 2024)
Indonesia as a country with the largest Muslim population in the world is faced with opportunities as well as challenges regarding the vision of Indonesia Emas 2045 and Demographic Divident 2050 where education including religious education (Islam) is one of the success factors. That way, as the vanguard, Islamic Religious Education (PAI) teachers have a strategic role in realizing this vision. This study aims to identify  the mindset of  today's PAI teachers facing the vision of Golden Indonesia 2045 and Demographic Divident 2050. The research method used is  literature review or  literature  research, which is a research design process that seeks to develop research practices that can build skills, meaning, and academic development. This study concludes that the resilience of PAI teachers in facing the vision of Indonesia Emas 2045 and Demographic Divident 2050 can be done through the following practical and strategic steps: 1) PAI teachers must have sensitivity to changes in attitudes and actions, be given space for expression, exploration, and existence, fostered massively, sustainably, and systematically to remain in accordance with the needs and challenges of today; and 2) PAI teachers must have a mindset Growth Mindset,  transformative mindset,  and sustainable mindset so as to design and implement quality learning.